PENGEMBANGAN SISTEM PENGUKURAN GELOMBANG ULTRASONIK UNTUK PENENTUAN KUALITAS BUAH MANGGIS (Gracinia mangostana L) - Jajang Juansah; I Wayan Budiastra; Suroso . (PERTETA, 2006)
ABSTRACT The research has been conducted to develop a measurement system of mangosteen quality by using an ultrasonic wave. The pulse signal cricuit has been used as a generating circuit of the measurement system. The pulse signal circuit consisted of timer circuit NE 555, monostabil, and amplife5r based on IC 741 with frequency of 50 kHz. The circuit of the ultrasonic wave receiver was developed based on the transistor and the IC 741. The interface and communications of data between the measurement system and the personal computer were carried out using a digital oscilloscope. The measurement system has been examined to determine the ultrasonic wave parameters including attenuation coeffiecient and impedance at the air medium and the mangostean. Keyword: attenuation coeffiecient, impedance, ultrasonic, mangostean.